Economic feasibility and long-term sustainability criteria on the path to enable a transition from fossil fuels to biofuels. - Perin,G; Jones,PR (Current Opinion in Biotechnology, 2019)
Currently the production of liquid biofuels relies on plant biomass, which in turn depends on the photosynthetic conversion of light and CO2 into chemical energy. As a consequence, the process is renewable on a far shorter time-scale than its fossil counterpart, thus rendering a potential to reduce the environmental impact of the transportation sector. However, the global economy is not intensively pursuing this route, as current generation biofuel production does not meet two key criteria: (1) economic feasibility and (2) long-term sustainability. Herein, we argue that microalgal systems are valuable alternatives to consider, although it is currently technologically immature and therefore not possible to reach criterion 1, nor evaluate criterion 2. In this review we discuss the major limiting factors for this technology and highlight how further research efforts could be deployed to concretize an industrial reality.